Paste heat-stable material and application thereof in transparent plastic hose

By using paste-like thermally stable materials composed of white oil and modified vapor-phase silica in transparent plastic hoses, an organic-inorganic composite stable system is formed, which solves the problems of poor transparency, poor early whiteness and unsatisfactory thermal stability effects, and achieves high transparency, long-term stability and environmentally friendly PVC hose.

CN120272021AInactive Publication Date: 2025-07-08HUIZHOU AIMSEA NEWWAY TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510509614.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing thermally stable materials are used in the preparation of transparent plastic hoses, and there are problems such as poor transparency, poor early whiteness and unsatisfactory thermal stability effects.

Method used

The paste-like thermally stable material consisting of white oil, modified vapor phase silica, zinc stearate, calcium stearate, cerium acetylacetonate, pentaerythritol aminoureamin pentaerythritol ester, epoxytetrahydrophthalate and pentaerythritol diphosphite distearate are used to form an organic-inorganic composite stable system to inhibit the thermal degradation and color change of PVC and improve long-term stability.

Benefits of technology

Effectively inhibit the long-term thermal degradation and color change of PVC, extend the initial whiteness, improve the optical and physical properties of the transparent hose, and achieve excellent heat-resistant aging performance and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005370801140000101
    Figure BDA0005370801140000101
Patent Text Reader

Abstract

The invention discloses a pasty heat-stable material and application thereof in a transparent plastic hose, and relates to the technical field of plastic pipes. The pasty thermal stable material is prepared by the following steps: pre-dispersing white oil and modified fumed silica to obtain a matrix; and adding the zinc stearate, the calcium stearate, the cerium acetylacetonate, the aminouracil maleic amide pentaerythritol ester, the epoxy tetrahydrophthalate and the pentaerythritol diphosphite distearate into the matrix, so as to obtain the pasty thermal stable material. The preparation method comprises the following steps: adding the zinc stearate, the calcium stearate, the cerium acetylacetonate, the aminouracil maleic amide pentaerythritol ester, the epoxy tetrahydrophthalate and the pentaerythritol diphosphite distearate into the matrix; the pasty heat-stable material prepared by the invention effectively inhibits long-term thermal degradation and color change of PVC, effectively prolongs the initial whiteness, can be widely applied to food-grade, medical-grade and industrial-grade transparent PVC hoses, improves the long-term stability of a PVC system, keeps the optical and physical properties of the transparent plastic hoses, and has a good application prospect. And excellent thermal aging resistance and environmental friendliness are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of plastic pipes, and particularly relates to a paste-like heat stabilizer material and its application in transparent plastic hoses. Background Art

[0002] Polyvinyl chloride (PVC) is one of the five general-purpose synthetic resins in the world, with its output ranking second only to polyethylene and ranking second in the world. PVC products have the characteristics of being light, soft, high in mechanical strength, resistant to chemical corrosion, insulating, and transparent, and are widely used in industries, agriculture, construction, packaging and other fields. However, PVC has a fatal weakness, that is, poor processing heat stability, and is prone to release hydrogen chloride gas when heated, resulting in a decline in its mechanical properties and a gradual darkening of its color. Therefore, stabilizers must be added during the production and processing of PVC. There are many types of heat stabilizers for PVC plastics, including heavy metal lead and cadmium heat stabilizers, calcium-zinc composite heat stabilizers (liquid / powder / paste), and organotin heat stabilizers. Among them, although lead and cadmium heat stabilizers have good performance, with the increasingly strict environmental protection requirements at home and abroad, their application fields have been greatly restricted. For organotin heat stabilizers, if evaluated only from the transparency and heat aging indexes, their performance is excellent; but they will have an annoying pungent smell for a long time, causing potential harm to the environment and human health.

[0003] China's industry is developing towards the direction of green environmental protection, low-carbon sustainability, and PVC heat stabilizers also conform to this trend and are developing towards non-toxic environmental protection, compound high-efficiency, and new multi-functional directions. The market of traditional heavy metal lead and cadmium salt heat stabilizers has gradually been replaced by composite calcium / zinc salts. However, the currently commercially available calcium / zinc heat stabilizers generally have problems of single variety and performance, and poor stabilization effect. When used in compound with other additives, they often reduce the transparency and mechanical properties of plastic hoses. Therefore, the existing heat stabilizer materials for plastic hoses have defects such as poor transparency, poor initial whiteness, and unsatisfactory heat stabilization effect, making the use of this technology very limited. Summary of the Invention

[0004] The purpose of the present invention is to provide a paste-like heat stabilizer material and its application in transparent plastic hoses, and solve the following technical problems:

[0005] When the existing heat stabilizer materials are used in the preparation of transparent plastic hoses, there are problems of poor transparency, poor initial whiteness, and unsatisfactory heat stabilization effect.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A paste-like heat stabilizer material, which is prepared by the following method:

[0008] Pre-disperse white oil and modified fumed silica to obtain a matrix;

[0009] Zinc stearate, calcium stearate, cerium acetylacetonate, semicarbazide pyrimidine maleamide pentaerythritol ester, epoxy tetrahydrophthalate, and dipentaerythritol distearate diphosphite are added to the above matrix to obtain a paste-like heat stabilizer material.

[0010] As a further aspect of the present invention: The mass ratio of the white oil, the modified fumed silica, the zinc stearate, the calcium stearate, the cerium acetylacetonate, the semicarbazide pyrimidine maleamide pentaerythritol ester, the epoxy tetrahydrophthalate, and the dipentaerythritol distearate diphosphite is 10-15:1-2:1-1.5:0.3-0.5:0.8-1.2:2.5-3.5:3-5:0.5-1.

[0011] As a further aspect of the present invention: The preparation method of the semicarbazide pyrimidine maleamide pentaerythritol ester includes the following steps:

[0012] Maleic anhydride and 6-amino-1,3-dimethyluracil are mixed and then added to tetrahydrofuran. After the reaction, tetrahydrofuran is removed, and after drying, semicarbazide pyrimidine maleamic acid is obtained;

[0013] The semicarbazide pyrimidine maleamic acid and pentaerythritol are dissolved in tetrahydrofuran. After the reaction, tetrahydrofuran is removed, and after drying, semicarbazide pyrimidine maleamide pentaerythritol ester is obtained.

[0014] As a further aspect of the present invention: The mass ratio of the maleic anhydride and the 6-amino-1,3-dimethyluracil is 1:1.5-2.

[0015] As a further aspect of the present invention: The mass ratio of the semicarbazide pyrimidine maleamic acid and the pentaerythritol is 1.7-2:1.

[0016] As a further aspect of the present invention: The preparation method of the modified fumed silica includes the following steps:

[0017] The fumed silica is activated at 110-115 °C to obtain activated fumed silica;

[0018] The activated fumed silica is added to a modifier for modification to obtain modified fumed silica.

[0019] As a further aspect of the present invention: The modifier is at least one of hexamethyldisilazane, dimethyldichlorosilane, or polydimethylsiloxane.

[0020] As a further aspect of the present invention: The modification temperature is 110-115 °C and the time is 90-100 min.

[0021] As a further solution of the present invention: the mass ratio of the fumed silica to the modifier is 100:1 - 1.5.

[0022] An application of the paste-like heat stabilizer material as described in any one of the above as a stabilizer in the preparation of plastic hoses, wherein the mass ratio of the paste-like heat stabilizer material to PVC is (2 - 4):100.

[0023] The beneficial effects of the present invention:

[0024] In the present invention, zinc stearate, calcium stearate and cerium acetylacetonate are selected as the main stabilizers, and rare earth β-diketone chelates Zn 2+ / Ca 2+ , which inhibits "zinc burning", and scavenges free radicals through the redox activity of cerium to improve long-term weather resistance. Semicarbazide pyrimidine maleamide pentaerythritol ester and epoxy tetrahydrophthalic acid ester are selected as auxiliary stabilizers, and pentaerythritol distearate diphosphite is selected as an antioxidant. Through free radical capture and synergistic antioxidant strategies, the release of HCl during the degradation of PVC is inhibited, the aging of PVC is delayed, and at the same time, the migration and precipitation behavior of the stabilizer are optimized to improve the long-term service life of the hose. Modified fumed silica is selected as the rheology modifier, and white oil is selected as the dispersion medium to form an organic-inorganic composite stabilization system. Through surface modification of nano-oxides and polymer antioxidants, a paste-like heat stabilizer material with high dispersibility and high compatibility is formed, which effectively inhibits the long-term thermal degradation and color change of PVC and effectively extends the initial whiteness. The paste-like heat stabilizer material obtained by the present invention can be widely applied to food-grade, medical-grade and industrial-grade transparent PVC hoses, improving the long-term stability of the PVC system, maintaining the optical and physical properties of the transparent hose, while achieving excellent heat aging performance and environmental friendliness, and providing technical support for the long-term stable application of high-end PVC hoses.

[0025] The semicarbazide pyrimidine maleamide pentaerythritol ester prepared by the present invention combines the HCl absorption of the pyrimidine ring, the antioxidant property of the maleamide, and the plasticizing function of the pentaerythritol ester. On the one hand, the semicarbazide pyrimidine maleamide pentaerythritol ester and the epoxy tetrahydrophthalic acid ester play an auxiliary stabilizing role. The semicarbazide pyrimidine maleamide pentaerythritol ester stabilizes the PVC chain segments through intramolecular hydrogen bonds. The pyrimidine ring directly absorbs free HCl, delaying the dehydrochlorination reaction. Moreover, it has a heat stabilization mechanism of polyol structure. The polyol structure absorbs HCl, and the hydroxyl groups contained in AMP can improve the long-term thermal stability of PVC by absorbing and neutralizing the HCl evolved from the degradation of PVC. At the same time, the synergistic effect of the polyol and the metal soap, and the complexation of the polyol and the metal chloride can inhibit the catalytic effect of zinc chloride on the dehydrochlorination of PVC during heating, preventing the autocatalytic degradation of PVC and prolonging the initial whiteness. Another auxiliary stabilizer, epoxy tetrahydrophthalic acid ester, efficiently neutralizes HCl through ring-opening reaction, while passivating the catalytic activity of the metal soap and inhibiting "zinc burning". In the early stage of the reaction, the semicarbazide pyrimidine maleamide pentaerythritol ester rapidly absorbs HCl during the initial degradation stage of PVC. In the middle and late stages of the reaction, it continuously neutralizes HCl with EATHP and stabilizes metal ions. On the other hand, the semicarbazide pyrimidine maleamide pentaerythritol ester and the pentaerythritol distearate diphosphite produce a synergistic antioxidant effect. The maleamide group in the semicarbazide pyrimidine maleamide pentaerythritol captures free radicals to block the oxidation chain reaction, inhibits the oxidative chain scission of PVC, and inhibits free radical initiation. The peroxide generated by the decomposition and oxidation of the diphosphite in the pentaerythritol distearate diphosphite prevents it from further initiating free radical reactions and blocks the accumulation of peroxides. The two produce a synergistic antioxidant effect.

[0026] The present invention also adds modified fumed silica. The fumed silica is uniformly dispersed in the oil phase. The silica forms a three-dimensional network structure, uniformly wrapping and fixing other additive particles in the network, avoiding sedimentation or phase separation, ensuring the thixotropy and storage stability of the paste, and avoiding sedimentation or caking. At the same time, when the heat stabilizer is added to the PVC resin matrix, the silica particles form a weak cross-linked network under static conditions, increasing the system viscosity and inhibiting the migration of additives; during processing, the shear force destroys the network, the viscosity decreases, promoting the uniform dispersion of the additives with the flowing molten PVC, making the dispersion between the additives and the polyvinyl chloride resin more uniform, enabling each additive to fully play its respective role, reducing the phase separation phenomenon of the heat stabilizer in the PVC matrix, achieving a uniform distribution at the stabilizer-resin interface, and through the hydrophobic modification of silica with hexamethyldisilazane, the modified silica is more easily dispersed in the non-polar PVC matrix, reducing the interfacial tension and making the additive distribution more uniform. On the other hand, the silica itself plays a certain weather resistance role, and the relatively small particle size of the fumed silica has a small impact on the transmittance, improving the optical transparency. Detailed implementation mode

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0028] The preparation method of semicarbazide pyrimidine maleamide pentaerythritol ester in Embodiment 1 comprises the following steps:

[0029] Add 9.8 g of maleic anhydride into a four-necked flask equipped with a thermometer, a condenser and a mechanical stirring device, heat up and liquefy it. When the temperature rises to 90 °C, add 15.5 g of 6-amino-1,3-dimethyluracil. After mixing evenly, add the solvent tetrahydrofuran. Continue to react for 5 h under mechanical stirring and then stop the reaction. Rotate and evaporate to remove the solvent tetrahydrofuran. After drying, obtain semicarbazide pyrimidine maleamic acid;

[0030] Add the 12.6 g prepared above into a four-necked flask equipped with a thermometer, a condenser reflux and a mechanical stirring device, and add the solvent tetrahydrofuran. Heat up to dissolve the semicarbazide pyrimidine maleamic acid. When the solution temperature reaches 160 °C, add 7 g of pentaerythritol and react for 2 h. Rotate and evaporate to remove the solvent tetrahydrofuran. After drying, obtain semicarbazide pyrimidine maleamide pentaerythritol ester.

[0031] The preparation method of modified fumed silica in Embodiment 2 comprises the following steps:

[0032] Activate fumed silica at 110 °C for 3 h to obtain activated fumed silica;

[0033] Disperse 1 g of hexamethyldisilazane in water to obtain a modifier. Add the above 100 g of activated fumed silica into the modifier at 110 °C and modify for 100 min. Filter by suction, wash with ethanol, and then dry in vacuum at 90 °C to obtain modified fumed silica.

[0034] The preparation method of modified fumed silica in Embodiment 3 comprises the following steps:

[0035] Activate fumed silica at 110 °C for 3 h to obtain activated fumed silica;

[0036] Disperse 1.5 g of hexamethyldisilazane in water to obtain a modifier. Add the above 100 g of activated fumed silica into the modifier at 110 °C and modify for 100 min. Filter by suction, wash with ethanol, and then dry in vacuum at 90 °C to obtain modified fumed silica.

[0037] A paste-like heat stabilizer in Embodiment 4 is prepared by the following method:

[0038] Pre-disperse 100 g of white oil and 12 g of the modified fumed silica obtained in Example 2 by high-speed shearing at 3000 rpm for 10 min to obtain a matrix;

[0039] Add 12 g of zinc stearate, 4 g of calcium stearate, 10 g of cerium acetylacetonate, 20 g of semicarbazide pyrimidine maleamide pentaerythritol ester obtained in Example 1, 40 g of epoxy tetrahydrophthalate and 8 g of pentaerythritol diphosphite distearate to the above matrix and mix at 500 rpm for 20 min to obtain a paste-like heat stabilizer.

[0040] Example 5 A paste-like heat stabilizer is prepared by the following method:

[0041] Pre-disperse 100 g of white oil and 12 g of the modified fumed silica obtained in Example 3 by high-speed shearing at 3000 rpm for 10 min to obtain a matrix;

[0042] Add 12 g of zinc stearate, 4 g of calcium stearate, 10 g of cerium acetylacetonate, 20 g of semicarbazide pyrimidine maleamide pentaerythritol ester obtained in Example 1, 40 g of epoxy tetrahydrophthalate and 8 g of pentaerythritol diphosphite distearate to the above matrix and mix at 500 rpm for 20 min to obtain a paste-like heat stabilizer.

[0043] Example 6 A paste-like heat stabilizer is prepared by the following method:

[0044] Pre-disperse 100 g of white oil and 15 g of the modified fumed silica obtained in Example 2 by high-speed shearing at 3000 rpm for 10 min to obtain a matrix;

[0045] Add 15 g of zinc stearate, 3 g of calcium stearate, 10 g of cerium acetylacetonate, 22 g of semicarbazide pyrimidine maleamide pentaerythritol ester obtained in Example 1, 45 g of epoxy tetrahydrophthalate and 6 g of pentaerythritol diphosphite distearate to the above matrix and mix at 500 rpm for 20 min to obtain a paste-like heat stabilizer.

[0046] Example 7 A paste-like heat stabilizer is prepared by the following method:

[0047] Pre-disperse 100 g of white oil and 15 g of the modified fumed silica obtained in Example 3 by high-speed shearing at 3000 rpm for 10 min to obtain a matrix;

[0048] Add 15 g of zinc stearate, 3 g of calcium stearate, 10 g of cerium acetylacetonate, 22 g of semicarbazide pyrimidine maleamide pentaerythritol ester obtained in Example 1, 45 g of epoxy tetrahydrophthalate and 6 g of pentaerythritol diphosphite distearate to the above matrix and mix at 500 rpm for 20 min to obtain a paste-like heat stabilizer.

[0049] The preparation method of comparative example 1 aminouracil maleamide pentaerythritol ester includes the following steps:

[0050] Add 9.8 g of maleic anhydride into a four-necked flask equipped with a thermometer, a condenser and a mechanical stirring device, heat up and liquefy it. When the temperature rises to 90 °C, add 15.5 g of 6-amino-1,3-dimethyluracil. After mixing evenly, add the solvent tetrahydrofuran, and continue to react for 5 h under mechanical stirring, then stop the reaction. Rotary evaporate to remove the solvent tetrahydrofuran, and after drying, obtain aminouracil maleamic acid.

[0051] The preparation method of comparative example 2 alcohol-unmodified paste-like heat stabilizer is as follows:

[0052] Add 100 g of white oil and 12 g of the modified fumed silica obtained in Example 2 into a high-speed shear pre-dispersion for 10 min at a rotation speed of 3000 rpm to obtain a matrix;

[0053] Add 12 g of zinc stearate, 6 g of calcium stearate, 10 g of cerium acetylacetonate, 20 g of 1-aminouracil maleamic acid obtained in Comparative Example 1, 40 g of epoxy tetrahydrophthalate and 8 g of pentaerythritol distearate diphosphite into the above matrix and mix at a rotation speed of 500 rpm for 20 min to obtain a paste-like heat stabilizer.

[0054] The preparation method of comparative example 3 alcohol-free paste-like heat stabilizer is as follows:

[0055] Add 100 g of white oil and 12 g of the modified fumed silica obtained in Example 2 into a high-speed shear pre-dispersion for 10 min at a rotation speed of 3000 rpm to obtain a matrix;

[0056] Add 12 g of zinc stearate, 6 g of calcium stearate, 10 g of cerium acetylacetonate, 40 g of epoxy tetrahydrophthalate and 8 g of pentaerythritol distearate diphosphite into the above matrix and mix at a rotation speed of 500 rpm for 20 min to obtain a paste-like heat stabilizer.

[0057] The preparation method of comparative example 4 fumed silica-unmodified paste-like heat stabilizer is as follows:

[0058] Add 100 g of white oil and 12 g of unmodified fumed silica in Example 2 into a high-speed shear pre-dispersion for 10 min at a rotation speed of 3000 rpm to obtain a matrix;

[0059] Add 12 g of zinc stearate, 6 g of calcium stearate, 10 g of cerium acetylacetonate, 20 g of 1-aminouracil maleamic acid obtained in Comparative Example 1, 40 g of epoxy tetrahydrophthalate and 8 g of pentaerythritol distearate diphosphite into the above matrix and mix at a rotation speed of 500 rpm for 20 min to obtain a paste-like heat stabilizer

[0060] Comparative Example 5 Without silica A paste-like heat stabilizer material was prepared by the following method:

[0061] 12 g of zinc stearate, 6 g of calcium stearate, 10 g of cerium acetylacetonate, 20 g of semicarbazide pyrimidine maleamide pentaerythritol ester obtained in Example 1, 40 g of epoxy tetrahydrophthalate, and 8 g of pentaerythritol distearate diphosphite were added to 100 g of white oil and mixed at 500 rpm for 20 min to obtain a paste-like heat stabilizer material.

[0062] Performance testing

[0063] Preparation of PVC transparent hose:

[0064] 100 parts by mass of PVC resin, 50 parts by mass of plasticizer, 3 parts by mass of the transparent paste-like heat stabilizer material obtained in Examples 4-7 or Comparative Examples 2-5, 0.5 part by mass of lubricant, and 0.1 part by mass of decolorizer were added to a 500 L Z-shaped twin-screw stirring kneader, heated with steam, kneaded for 45-50 min, and discharged when the temperature reached 100-110 °C to obtain a mixture;

[0065] The above mixture was added to a granulator and extruded into pellets. The temperature of zone 1 was set at 80-90 °C, the temperature of zone 2 was set at 130-140 °C, the temperature of zone 3 was set at 140-150 °C, and the temperature of the die head was set at 150-160 °C to obtain masterbatch;

[0066] The above masterbatch was extruded into a tube. The temperature of zone 1 was set at 85-95 °C, the temperature of zone 2 was set at 145-155 °C, the temperature of zone 3 was set at 155-165 °C, and the temperature of zone 4 was set at 165-175 °C to obtain PVC transparent hoses added with different paste-like heat stabilizer materials.

[0067] Congo red test: Referring to the standard of GB / T 2917.1-2002 "Determination of Hydrochloric Acid and Any Other Acidic Products Evolved at High Temperatures from Blends and Products Based on Homopolymers and Copolymers of Vinyl Chloride - Congo Red Method", the static thermal stability performance of PVC was determined. Static thermal stability refers to the thermal stability effect of PVC under the action of only heat or heat and air. 10 g of PVC and 0.3 g of the paste - like thermal stability materials obtained in Examples 4 - 7 or Comparative Examples 2 - 5 were mixed evenly, and then evenly poured into the bottom of 4 test tubes. Take the test tube plug with a thin glass tube inserted, roll one end of the Congo red test paper and insert it into the thin glass tube, then plug the test tube with the plug, and adjust the position of the thin glass tube in the plug so that the end of the Congo red test paper in the test tube is 25 mm away from the surface of the sample. The prepared test tubes were immersed in an oil bath at 180 °C, and the surface of the sample was at the same height as the surface of the oil bath medium. When PVC degrades by heat, HCl gas is generated. As the HCl gas accumulates continuously, it causes a color change reaction of the Congo red test paper in the test tube. Observe the color change of the Congo red test paper, record the elapsed time from red to blue of the test paper color, and take the arithmetic mean of the results. This value is the stabilization time of the PVC sample; the test results are shown in Table 1;

[0068] Thermal aging test: A method to observe the change of PVC color over time under certain temperature conditions. During the degradation process, not only does the PVC molecular chain release HCl, but also the formation of C = C double bonds occurs, and the number of C = C double bonds increases rapidly with the progress of the degradation reaction, thus forming a conjugated polyene system, which macroscopically shows that the color of the PVC product becomes darker. Therefore, the degree of thermal degradation of PVC can be reflected by the degree of color change of PVC. By observing the depth and rate of change of the PVC color, the static thermal stability performance of PVC can be judged. The PVC sample was cut into small rectangles of 30 * 20 mm and placed on a stainless - steel tray, and then placed in an aging test chamber at 180 °C for aging. Observe the color change situation, and take samples and take pictures every 10 min for recording until the PVC sample turns black; record the time of the initial whiteness of the PVC sample and the time when it turns black during aging; the test results are shown in Table 1;

[0069] Transparency test: Measure the light transmittance of the PVC transparent hose on a light transmittance / haze tester; the test results are shown in Table 1;

[0070] Hose tensile strength test: The PVC transparent hose added with the transparent paste - like thermal stability materials obtained in Examples 4 - 7 and Comparative Examples 2 - 5 was subjected to a tensile strength test in accordance with GB / T 528 - 2009; the test results are shown in Table 1;

[0071] Hose elongation at break test: The PVC transparent hose added with the transparent paste - like thermal stability materials obtained in Examples 4 - 7 and Comparative Examples 2 - 5 was subjected to an elongation at break test in accordance with GB / T 1040.1 - 2006; the test results are shown in Table 1;

[0072] Table 1: Statistical Table of Performance Test Data of Specimens in Examples 4-7 and Comparative Examples 2-5

[0073]

[0074] As can be seen from Table 1, for the transparent paste-like heat stability materials prepared in Examples 4-7 of the present invention, they can effectively inhibit the long-term thermal degradation and color change of PVC, effectively extend the initial whiteness, improve the long-term stability of the PVC system, and at the same time ensure the optical and physical properties of the transparent hose. In Comparative Example 2, the structure of pentaerythritol was not introduced, and the initial whiteness of the obtained transparent paste-like heat stability material decreased, and the long-term thermal stability also decreased. In Comparative Example 3, semicarbazide pyrimidine maleamide pentaerythritol ester was not added, and the initial whiteness and long-term thermal stability of the obtained transparent paste-like heat stability material decreased significantly. In Comparative Example 4, the fumed silica was not modified, and the transparency of the obtained transparent paste-like heat stability material decreased. In Comparative Example 5, fumed silica was not added, and the properties of the obtained transparent paste-like heat stability material all decreased. It shows that the semicarbazide pyrimidine maleamide pentaerythritol ester added in the present invention can play a good role in extending the initial whiteness, improving the long-term thermal stability and antioxidant performance, and the added modified fumed silica can enable each additive to fully exert its respective functions.

[0075] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.

[0076] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art of this industry should understand that the present invention is not limited by the above embodiments. What is described in the above embodiments and the specification only illustrates the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed.

Claims

1. A paste-like heat-stable material, characterized in that, The paste-like heat stabilizer material is prepared by the following method: Pre-disperse white oil and modified fumed silica to obtain a matrix; Add zinc stearate, calcium stearate, cerium acetylacetonate, semicarbazide pyrimidine maleamide pentaerythritol ester, epoxy tetrahydrophthalate, and pentaerythritol distearate diphosphite into the above matrix to obtain the paste-like heat stabilizer material.

2. The paste-like heat-stable material according to claim 1, characterized in that, The mass ratio of the white oil, the modified fumed silica, the zinc stearate, the calcium stearate, the cerium acetylacetonate, the semicarbazide pyrimidine maleamide pentaerythritol ester, the epoxy tetrahydrophthalate, and the pentaerythritol distearate diphosphite is 10 - 15:1 - 2:1 - 1.5:0.3 - 0.5:0.8 - 1.2:2.5 - 3.5:3 - 5:0.5 - 1.

3. The paste-like heat-stable material according to claim 1, characterized in that, The preparation method of the semicarbazide pyrimidine maleamide pentaerythritol ester includes the following steps: Mix maleic anhydride and 6-amino-1,3-dimethyluracil, add tetrahydrofuran, remove tetrahydrofuran after the reaction, and obtain semicarbazide pyrimidine maleic acid after drying; Dissolve the semicarbazide pyrimidine maleic acid and pentaerythritol in tetrahydrofuran, remove tetrahydrofuran after the reaction, and obtain semicarbazide pyrimidine maleamide pentaerythritol ester after drying.

4. The paste-like heat-stable material according to claim 3, characterized in that, The mass ratio of the maleic anhydride and the 6-amino-1,3-dimethyluracil is 1:1.5 - 2.

5. The paste-like heat-stable material according to claim 3, characterized in that, The mass ratio of the semicarbazide pyrimidine maleic acid and the pentaerythritol is 1.7 - 2:

1.

6. The paste-like heat-stable material according to claim 1, characterized in that, The preparation method of the modified fumed silica includes the following steps: Activate fumed silica at 110 - 115 °C to obtain activated fumed silica; Add the activated fumed silica into a modifier for modification to obtain the modified fumed silica.

7. The paste-like heat-stable material according to claim 6, characterized in that, The modifier is at least one of hexamethyldisilazane, dimethyldichlorosilane, or polydimethylsiloxane.

8. The paste-like heat-stable material according to claim 6, characterized in that The temperature of the modification is 110 - 115 °C and the time is 90 - 100 min.

9. The paste-like heat-stable material according to claim 7, characterized in that, The mass ratio of the fumed silica and the modifier is 100:1 - 1.

5.

10. Use of the paste-like heat-stable material according to any one of claims 1-9 as a stabilizer in the preparation of a transparent plastic hose, characterized in that, The mass ratio of the paste-like heat stabilizer material to PVC is (2 - 4):100.

Citation Information

Patent Citations

  • Hexa-methyldisilazane graft modified silicon dioxide and preparation method thereof

    CN101429290A

  • Uracil maleamic polyol ester and preparation method and application thereof

    CN109020899A

  • Composite calcium-zinc heat stabilizer composition as well as preparation method and application thereof

    CN115232363A